Jesus as the Messiah: A Biblical Theology Perspective - Tonny Andrian Stefanus; Muner Daliman (Jurnal Teologi (JUTEOLOG), 2026)
This study presents a biblical-theological exploration of Jesus as the Messiah by examining key New Testament passages that reveal His identity, mission, and redemptive authority. The purpose of the research is to clarify how the Gospel of Matthew integrates faith, salvation, and healing within the ministry of Jesus, while also demonstrating the continuity between Old Testament covenant promises and their fulfillment in Christ. Using a qualitative biblical-theology method, the study conducts textual analysis, canonical tracing, thematic synthesis, and comparative evaluation of selected passages from the Gospels and Acts.The findings affirm that Scripture consistently portrays Jesus as the promised Messiah and the divine Son of Man who possesses authority to forgive sins and bring holistic restoration. Faith in Christ is shown to be the foundation for both salvation and healing, revealing the unity of God’s redemptive work. The study concludes that recognizing Jesus as the Messiah is essential for understanding the fullness of God’s saving activity. This research contributes to theological scholarship by offering an integrated perspective that connects Christ’s healing ministry, covenant fulfillment, and salvific mission within the broader canonical narrative.